IMPLEMENTATION OF DISCOVERY LEARNING MODEL INTEGRATED WITH SCIENCE GENERIC SKILLS TO IMPROVE HIGHER ORDER THINKING SKILLS ON THERMOCHEMISTRY MATERIAL - Gulo, Yiska Hairani; Sinaga, Marudut (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
This study aims to determine the effect of Evaluation of Prior Knowledge (EPA) and Learner Worksheets (LKPD) on students' higher order thinking skills expressed in the form of Evaluation of Learning Outcomes (EHB) using the Discovery Learning (DL) learning model integrated with Science Generic Skills (KGS) on Thermochemical Material. The research was conducted at SMA Swasta Methodist Tanjung Morawa T.A 2023/2024 with all XI PSP classes as the population and XI PSP classes who took Chemistry subjects on Thursdays obtained by purposive sampling technique as research samples. The research design used is a double paradigm with two independent variables, namely; EPA and LKPD, and one dependent variable namely; EHB. The test instruments used in this study were EPA, LKPD and EHB as many as 25 items developed by previous researchers and nontest instruments in the form of student observation sheets. The results showed that there was a significant influence between EPA and LKPD on EHB. From the independent t-test, which has been carried out, students with high EPA obtained higher EHB than students with low EPA.Keywords: DL integrated KGS, EPA, LKPD, EHB, Thermochemistry